2003
DOI: 10.1094/pdis.2003.87.12.1500
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuations of Phytophthora and Pythium spp. in Components of a Recycling Irrigation System

Abstract: Stringent standards of water quality have prompted many horticultural enterprises to limit pollutant discharge associated with nutrient and pesticide applications. Collecting and recycling effluent is a method that has been implemented by many operations to contain pollutants; however, plant pathogens may be spread through recycled effluent. In this study, Phytophthora and Pythium spp. present in a water-recycling irrigation system at a perennial container nursery in southwestern Virginia were characterized us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
0
13

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 20 publications
4
51
0
13
Order By: Relevance
“…found in irrigation water at different depths. For example, Bush et al (2003) found this species on the surface of irrigation water and at depths of 1 and 1.5 m. Two species of Phytophthora were isolated from the surface of 10 irrigation channels in the Culiacán Valley. In the channels where Phytophthora was found, P. hydropathical was found in only 40 %, in 30 % only P.drechsleri, and in 30 %, both species ( Figure 6).…”
Section: Fully Bilingualmentioning
confidence: 99%
See 3 more Smart Citations
“…found in irrigation water at different depths. For example, Bush et al (2003) found this species on the surface of irrigation water and at depths of 1 and 1.5 m. Two species of Phytophthora were isolated from the surface of 10 irrigation channels in the Culiacán Valley. In the channels where Phytophthora was found, P. hydropathical was found in only 40 %, in 30 % only P.drechsleri, and in 30 %, both species ( Figure 6).…”
Section: Fully Bilingualmentioning
confidence: 99%
“…El material vegetal fue lavado con agua corriente y desinfestado con etanol al 70 % durante 30 s antes de ser colocado en las trampas. Las trampas permanecieron en la superficie de los canales de riego durante 48 h (Bush et al, 2003). Posteriormente, las trampas se colectaron y se trasladaron al laboratorio.…”
Section: Colecta De Aisladosunclassified
See 2 more Smart Citations
“…Bush et al (2003) presented that recycled irrigation water from harbors contained substantial densities of pathogens and Hong and Moorman (2005) reported the presence of 17 Phytophthora sp., 26 Pythium sp., 27 genera of fungi, 8 species of bacteria, 10 viruses and 13 species of plant parasitic nematodes in irrigation water from ponds, rivers, canals, streams, lakes, runoff water, etc. These facts explain why chlorine is used for disinfection of irrigation water (Cayanan et al 2009).…”
Section: Introductionmentioning
confidence: 99%